The Forms and Sources of Cytokinins in Developing White Lupine Seeds and Fruits - Emery, R.J. Neil (American Society of Plant Physiologists, 2000)
A comprehensive range of cytokinins (CK) was identified and quantified by gas chromatography-mass spectrometry in tissues of and in xylem and phloem serving developing white lupine (Lupinus albus) fruits. Analyses were initiated at anthesis and included stages of podset, embryogenesis, and seed filling up to physiological maturation 77 d post anthesis (DPA). In the first 10 DPA, fertilized ovaries destined to set pods accumulated CK. The proportion of cis-CK:trans-CK isomers was initially 10:1 but declined to less than 1:1. In ovaries destined to abort, the ratio of cis-isomers to trans-isomers remained high. During early podset, accumulation of CK (30–40 pmol ovary(−1)) was accounted for by xylem and phloem translocation, both containing more than 90% cis-isomers. During embryogenesis and early seed filling (40–46 DPA), translocation accounted for 1% to 14% of the increases of CK in endosperm (20 nmol fruit(−1)) and seed coat (15 nmol fruit(−1)), indicating synthesis in situ. High CK concentrations in seeds (0.6 μmol g(−1) fresh weight) were transient, declining rapidly to less than 1% of maximum levels by physiological maturity. These data pose new questions about the localization and timing of CK synthesis, the significance of translocation, and the role(s) of CK forms in reproductive development.